Automatic control for food processing systems - Moreira, Rosana G. (Aspen Engineering, 2001)
Introduction - Food processing systems - Background - Process dynamics modeling - Multivariable systems - Model predictive control - Adaptive control - Statical process control and intelligent controllers - Instrumentation.